Manejo integrado plagas en el cultivo del algodonero en el Valle del Cauca. - Tróchez Parra, Adolfo L.; Díaz Mantilla, Ana Elizabeth; García Roa, Fulvia A. (Corporación Colombiana de Investigación Agropecuaria - CORPOICA, 2018)
Algodón-Gossypium herbaceum